Hospitality work and the sociality of affective labour. Issue 1 (January 2023) - Farrugia, David; Coffey, Julia; Threadgold, Steven; Adkins, Lisa; Gill, Ros; Sharp, Megan; Cook, Julia
This article explores how the social relationships of precarious workers contribute to employment and labour practices in the hospitality industry. In so doing, it contributes to theoretical discussions about the nature of post-Fordist labour, and to studies of the social relations of precarity as they are enacted in workers' intimate lives. Empirically, the article describes a distinctive mode of interpersonal negotiation and sociality practised by workers that is connected to the requirement that workers be 'fun' at work to facilitate consumption and to support the labour of co-workers. This sociality also shapes access to employment. However, the way that this takes place sheds light on divisions within the service labour force, in which employment opportunities are distributed through a social 'scene' that excludes migrant and ethnic minority workers. Involvement in this scene places the relationship between the public and the private in workers' social lives into a constant tension, but exclusion increases vulnerability to poor working conditions and exploitation. The article concludes by arguing that the relationship between the public and the private in the practice of affective labour is not dissolved so much as posed as a problem that workers must negotiate within the disciplinary requirements of labour in specific industries and the modes of embodied inequality shaping the service labour force.